Sinema Terbuka Sebagai Ruang Ketiga di Jakarta - Tramilia Salsabila Utami; Nina Carina (Jurusan Arsitektur dan Perencanaan, 2020)
Cinema in Jakarta generally located in a shopping mall in Jakarta. Cinema nowadays becomes a destination for people but not yet become a third place. The lack of third place in Jakarta that can provide a place for gathering, as a meeting point, and entertainment makes Jakarta residents used commercial building as a third place. Looking at the design and program a cinema that can meet the conditions and characteristics of a third place by looking at the phenomenon cinema in Jakarta. Open cinema takes layar tancap concept or